Sleep quality using Pittsburgh Sleep Quality Index among preclinical undergraduate medical students: A descriptive cross-sectional study from Chitwan Medical College - Timilsina, Sameer; Bhandari, Adarsh; Tripathi, Anurag; Prasad Neupane, Krishna; Khetan, Vriddhi; Bokati, Yojana; Dhungana, Shiwanu; Karkee, Shristi; Karki Silwal, Sahara (Journal of Chitwan Medical College, 2025)
Introduction: The demanding academic rigours of stressful medical studies can cause circadian rhythm disturbances that negatively impact students' mental and physical health. Improper sleep affects academic performance and overall well-being. Studies report a higher prevalence of sleep disturbances among medical students. This study examines sleep habits of preclinical undergraduate medical students at a private medical college in Nepal. Method: This descriptive cross-sectional study was conducted among 186 preclinical undergraduate medical students at Chitwan Medical College, Nepal between Apr to May 2024. Data for demographic variables and sleep quality using the Pittsburgh Sleep Quality Index (PSQI) was collected using links generated via Google Forms following ethical clearance (Ref- CMC-IRC/080/081-087). The chi-square test was used to explore the association between sleep habits and demography of students (gender, academic years one and two). The level of significance was set at 5%. Result: Out of 186 students, PSQI score >5 (indicating poor sleep quality) was found in 116(62.4%). The median bedtime was 11:00 PM and the wakeup time was 07:00 AM. The mean sleep hours were 6.63±1.19 hours. About 10% of study participants took medicine for sleep-related issues. Conclusion: In this study, the prevalence of poor-quality sleep was high among preclinical undergraduate medical students at Chitwan Medical College. Sleep hygiene education may improve the sleep quality of medical students.